Neighbourhood integration in european multi-ethnic cities. Evidence from the Geitonies project - Fonseca,Maria Lucinda (2013)
This special issue of Finisterra is based on the findings of the GEITONIES project, and intends to shed some light on questions relating to ethnic diversity, social relations and participation in urban settings. The research was conducted in 6 European cities: Lisbon, Bilbao, Thessaloniki Rotterdam, Vienna and Warsaw and the neighbourhood context was adopted as the field of research. A random survey was implemented to 3600 residents in 18 neighbourhoods in the six cities. The papers included in this special issue of Finisterra - Revista Portuguesa de Geografia, focus on processes of change and social relations at the neighbourhood level and stress the role of place and time in the development of positive inter-group contacts, representations and integration.